The Urgence of Writing Awig's Pararem in Increasing Community Legal Awareness in Traditional Village Pelem Gede, Tabanan - I Ketut Sukadana; Luh Putu Suryani; Ni Made Puspasutari Ujianti; I Ketut Jika; Kadek Ayu Surya Dwi Utami (Community Service Journal of Law, 2023)
Desa Adat is a traditional village in Bali which has been autonomous since its inception. Each Traditional Village has its own management and assets, and has the authority to make rules, known as awig-awig and/or pararem. It turns out that the program partners do not yet have pararem panyahcah awig as rules for implementing awig-awig. By providing accessible and relevant information about legal rights, responsibilities, and processes, "Pararem Panyahcah Awig" equips community members with the knowledge they need to navigate legal matters effectively. s to emphasize the importance and necessity of documenting and disseminating the local customary laws, known as Awig's Pararem, within the context of the Traditional Village Pelem Gede in Tabanan. The method used in this service program is by: (1) giving lectures or legal counseling about the importance of a pararem panyahcah awig in life in a traditional village, (2) carrying out focus group discussions (FGD) on pararem drafts, and (3) provide assistance in making traditional village pararem. The result of this program activity is the compilation of an awig pararem with a total of 42 Pawos, in accordance with the awig-awig mandate set forth in Pawos-Pawos (article). With the pararem panyahcah awig, the community will be wiser in acting and behaving in their association in society. Therefore, it will indirectly increase legal awareness.